2015
DOI: 10.1371/journal.pone.0121422
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Organic Solvents Used in Dry Cleaning Reduces Low and High Level Visual Function

Abstract: PurposeTo investigate whether exposure to occupational levels of organic solvents in the dry cleaning industry is associated with neurotoxic symptoms and visual deficits in the perception of basic visual features such as luminance contrast and colour, higher level processing of global motion and form (Experiment 1), and cognitive function as measured in a visual search task (Experiment 2).MethodsThe Q16 neurotoxic questionnaire, a commonly used measure of neurotoxicity (by the World Health Organization), was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 93 publications
1
9
2
1
Order By: Relevance
“…This discrepancy among studies may be explained by differences in solvent exposures and in some cases less control for other factors known to affect visual contrast sensitivity (e.g., alcohol use, diabetes). (55, 58) Therefore, in contrast with the conclusions of previous reviews(13) the current study did not reveal an association between chronic solvent exposure and indicators of either cognitive, motor, or visual contrast function.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This discrepancy among studies may be explained by differences in solvent exposures and in some cases less control for other factors known to affect visual contrast sensitivity (e.g., alcohol use, diabetes). (55, 58) Therefore, in contrast with the conclusions of previous reviews(13) the current study did not reveal an association between chronic solvent exposure and indicators of either cognitive, motor, or visual contrast function.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall multivariate analyses for the domains of attention, working memory, and visual memory did not support that exposed subjects exhibited a consistent pattern of impaired neurobehavioral function in any domain. Although several previous studies reported reduced visual contrast sensitivity as an indicator of solvent induced neurotoxicity(51, 5558), the current study also did not reveal any significant differences in contrast sensitivity at any spatial frequency. This discrepancy among studies may be explained by differences in solvent exposures and in some cases less control for other factors known to affect visual contrast sensitivity (e.g., alcohol use, diabetes).…”
Section: Discussioncontrasting
confidence: 96%
“…However, the analysis of this unique macrobotanical evidence has concentrated largely on those plant remains that later became the first domesticates (i.e. wild cereals and grasses) [ 28 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…En general, los solventes orgánicos pueden afectar el desempeño neurocognitivo y los efectos de la exposición crónica dependen de la precisión del test neurocognitivo y del índice de composición corporal. Boon, & Khuu, 2015;Lotti, Bleecker, & Aminoff, 2015), as well as changes in motor, sensory and neurocognitive functions (Morrow & Scott, 2002;Sabbath et al, 2014). A decline in cognitive ability may be a predictor of the development of a number of neurodegenerative disorders such as dementias, for example (Blazer, Yaffe, & Liverman, 2015).…”
Section: Relación Entre Desempeño Neurocognitivo Y Composición Corporunclassified